Budgeting basics and beyond - Shim, Jae K.; Siegel, Joel G.; Shim, Allison I., 1984- (Hoboken, N.J. : Wiley, 2012)
"Budgeting Basics and Beyond, 4th Edition is a practical, easy-to-use problem-solver and up-to-date reference tool for today's financial and nonfinancial managers in public practice and private industry. It is packed with case studies, illustrations, exhibits, forms, checklists, graphs, samples, and worked-out solutions to a wide variety of budgeting, planning, and control problems. It is a truly valuable resource guaranteed to make the budgeting process effective and hassle-free for all managers who use it. The new edition includes new cost cutting strategies, software packages updates, cloud computing nd, new use of Excel for exponential smoothing, Minitab and SPSS, and updates on cash flow software. The book also includes financial planning and new types of financial modeling, variance analysis, Web-based budgeting, active budgeting illuminating "what-if" analyses throughout, spreadsheet applications, break-even analysis, project analysis, and capital budgeting"--
Chapter 23: Managers' Performance and Balanced Scorecard: Evaluation at the Division LevelChapter 24: Budgeting for Service Organizations: Special Features; Chapter 25: Budgeting for Nonprofit Organizations: Diverse Types; Chapter 26: Using Management Games for Executive Training; Appendix I: Future and Present Value Tables; Appendix II: Statistical Table; Glossary of Budgeting and Planning Terms; Index.
Includes index.
Machine generated contents note: About the Authors. Preface. Chapter 1: The What and Why of Budgeting: An Introduction. Chapter 2: Strategic Planning and Budgeting: Process, Preparation and Control. Chapter 3: Administering the Budget: Reports, Analyses, and Evaluations. Chapter 4: Break-even and Contribution Margin Analysis: Profit, Cost, and Volume Changes. Chapter 5: Profit Planning: Targeting and Reaching Achievable Goals. Chapter 6: Master Budget: Genesis of Financial Forecasting and Profit Planning. Chapter 7: Cost Behavior: Emphasis on Flexible Budgets. Chapter 8: Evaluating Performance: The Use of Variance Analysis. Chapter 9: Manufacturing Costs: Sales Forecasts and Realistic Budgets. Chapter 10: Marketing: Budgeting for Sales, Advertising, and Distribution. Chapter 11: Research and Development: Budgets for a Long-term Plan. Chapter 12: General and Administrative Costs: Budgets for Maximum Productivity. Chapter 13: Capital Expenditures: Assets to Be Bought, Sold, and Discarded. Chapter 14: Forecasting and Planning: Reducing Risk in Decision Making. Chapter 15: Moving Averages and Smoothing Techniques: Quantitative Forecasting. Chapter 16: Regression Analysis: Popular Sales Forecast System. Chapter 17: Cash Budgeting and Forecasting Cash Flow: Two Pragmatic Methods. Chapter 18: Financial Modeling: Tools for Budgeting and Profit Planning. Chapter 19: Using Software Packages and E-Budgeting: Computer-based Models, Spreadsheets, and Web-based System. Chapter 20: Capital Budgeting: Selecting the Optimum Long-term Investment and Real Options. Chapter 21: Budgeting for Cost Management: Activity-based Budgeting and Life-cycle Budgeting. Chapter 22: Zero-base Budgeting: Priority Budgeting for Best Resource Allocation. Chapter 23: Managers' Performance and Balanced Scorecard: Evaluation on the Division Level. Chapter 24: Budgeting for Service Organizations: Special Features. Chapter 25: Budgeting for Nonprofit Organizations: Diverse Types. Chapter 26: Using Management Games for Executive Training. Appendix I: Present and Future Value Tables. Appendix II: Statistical Table. Glossary of Budgeting and Planning Terms. Index.
Includes bibliographical references and index.
Keywords: Budget in business; Budgets; Financial Management; BUSINESS & ECONOMICS -- Budgeting; Budget in business; Electronic books; Electronic books